Influence of Online Social Networking on Entrepreneurial Intention Among UTHM Diploma Students - Nur Aini Syakirah Mohd Fazil,; Siti Zuraidah Athira Amran,; Pammella Carol,; Ghazali, Norliza (Multidisciplinary Applied Research and Innovation, 2024)
Online social networking (OSN) has increasingly attracted university students’ attention and has become a platform for students to do business and engage with entrepreneurs. Furthermore, it has encouraged them to have entrepreneurial intentions. Since online social networking has become a vital part of our daily lives where everything is done online, especially for young entrepreneurs with online business accounts, this study identified how online social networking affects the entrepreneurial intentions of UTHM Diploma students. In this research, the aim is to define the influence of online social networking on entrepreneurial intention among UTHM diploma students, identify the online social networking factors of entrepreneurial intention among UTHM diploma students, and determine the relationship between online social networking and entrepreneurial intention among UTHM diploma students. This research is done among the current active UTHM Diploma students. Google Forms are used to distribute the questionnaire, and the Statistical Package for Social Sciences (SPSS) is used to analyse the data in this study. According to the results obtained, most of the students utilise online social networks to communicate with entrepreneurs and are motivated to pursue entrepreneurial ventures. As a summary, it can be concluded that the diploma students at UTHM are interested in entrepreneurial intention and that factors such as interest lead them to pursue it more.